(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Emergency repair of complicated inguinal hernia remains contentious, with ongoing debate between tissue-based herniorrhaphy and mesh hernioplasty. This randomized controlled trial compared outcomes of both techniques in the emergency setting. Methods: The study will be conducted between August 2024 and February 2025 and will randomize 216 patients aged between 20 and 60 years with complicated inguinal hernia (symptoms >3 months) into herniorrhaphy (n=108) and hernioplasty (n=108) groups. Primary endpoints were postoperative complications, recurrence, hospital stay, and recovery profile. Results: The two groups were similar in terms of demographics. Hospital stay was much shorter in hernioplasty (5days; IQR 4-6) compared to herniorrhaphy (6days; IQR 5-8; p=0.002). Hernioplasty was also superior in time to ambulation (28 vs 36 hours; p=0.01) and back to normal diet (2 vs 2 days; p=0.03). The rates of wound infection were the same (herniorrhaphy 14.8%, hernioplasty 10.2%; p=0.27), and seroma was more frequent in the mesh (12.0% vs 4.6%; p=0.04). Most importantly, recurrence 6 months later was much lower in the case of hernioplasty (2.8 %vs 10.2%; p=0.02). The rates of chronic pain were low and similar. Conclusion: Emergency hernioplasty is safe and effective with a faster recovery, less hospitalization, and greatly reduced early recurrence as compared to herniorrhaphy. Mesh reinforcement is desirable in clean or contaminated emergency cases where bowel viability is specific and contamination is limited.